PW 1937 Socioeconomic differences in equipment-based playground injuries in ontario: a population-based study. (November 2018) - Siladi, Tanita; Richmond, Sarah A; Pyper, Evelyn; Wilton, Andrew S; Macpherson, Alison
Abstract : Background: One of the most fundamental and formative aspects of childhood is play- which in Canada, frequently takes place on playgrounds. Previous research has shown that upgrading playground structures to comply with the Canadian Standards Association (CSA) standards, mitigates the effect of socioeconomic-status (SES) on playground injuries. Ontario government regulations require playgrounds to meet CSA standards if children in daycare use them. Objective The objective of this study was to examine the relationship between children's falls from playground equipment and SES following compliance with CSA standards, and to examine injury trends from 2008–2015 in Ontario. Methods: Population-based data from the Institute for Clinical Evaluative Sciences was used, and includes all Emergency-Department (ED) visits and hospitalizations with the ICD-10 code W09 representing falls from playground equipment. The denominator for this study was the number of children in Ontario (1–19 years) and rate per 1 00 000 was calculated from 2008–2015. SES was based on income-quintile of the child's neighbourhood. Results: There were 7, 505 ED visits in 2008 vs 10 426 in 2015 (39% increase) and injury-rates demonstrated that children that live in the poorest (Quintile-1) neighbourhoods had lower playground injury rates than those in Quintile-5 (rates of 256.26, 334.3 respectively). Both income-quintiles (1 and 5) had a 45% increase over the study period and the five-to-nine age group was seen to be at highest risk of injury (average rate 551.6). Conclusion: The results suggest that playground injury rates in Ontario, where most playgrounds meet the CSA standards, increase by SES status, with the wealthiest children at highest risk of injury. Differences recorded in this study may reflect differences in exposure to playgrounds (i.e., wealthier children may have more exposure to playgrounds). However, the changes to the SES/playground injury association suggests that policy changes to the built environment can modify vulnerable children's incidence of injury.